Study on the effectiveness of silica fume-derived activator as a substitute for water glass in fly ash-based geopolymer. (1st July 2022) - Cheng, Yaqian; Cong, Peiliang; Zhao, Qi; Hao, Hongjie; Mei, Linna; Zhang, Anyu; Han, Zhiyu; Hu, Miao
Abstract: To continuously promote the development of geopolymer materials, an alternative water glass (AWG) about silica fume-derived (SF–NaOH) was synthesized. The study of this activator is beneficial to reduce the production cost of geopolymer and the adverse impact on environment. So the properties of fly ash (FA)-based geopolymers activated by AWG were studied, comparing with that activated by NaOH and traditional alkali activators (water glass and NaOH). The results showed that the AWG was a potential and efficient activator because the 90 d compressive strength of FA-based geopolymer activated by AWG could exceed 58 MPa at room temperature. The Initial setting time of FA-based geopolymer could be reduced nearly 5 times with the SF content. The degree of fly ash reaction proved that the alkali concentration played a leading role in the dissolution of the precursor. The activity of the AWG depends on the relative content of Q 1 and Q 2 units (SiO2 tetrahedron). The SEM analysis illustrated that high NaOH concentration and appropriate amount of available silica could significantly improve the reaction degree of FA, resulting in abundant alkali aluminosilicate gels and dense matrix structure. Graphical abstract: Image 1 Highlights: The AWG was an effective activator for producing sustainable FA-based geopolymer. The AWG accelerated the geopolymerization with the active silica content. The activation effect of AWG was similar with the WG + NaOH but better than that NaOH. The action mechanism of AWG depended on the alkali concentration and the type and content of silica tetrahedron.